Effects of epiphyseal proteins and melatonin on the blood biochemical parameters of fluoride-intoxicated rats - Bharti, V.K.; Srivastava, R.S. (Нейрофизиология, 2010)
We examined the effects of fluoride intoxication on certain blood plasma biochemical indices in rats. Forty-eight adult female Wistar rats weighing 123-142 g were divided into eight groups: two control groups (0 and 28 days) and six experimental groups, namely sham-injected animals (vehicle), those injected with pineal proteins (PP) and melatonin (Mel), intoxicated with fluoride (F), and also F⁺PP and F⁺Mel groups. Fluoride (150 ppm, per os administration with drinking water), melatonin (10 mg/kg, i.p.), and PP (100 μg/kg, i.p.) were administered daily for 28 days. Blood samples were collected at the end of experiments to estimate plasma [Na⁺] and [K⁺], alkaline phosphatase (ALP) activity, and levels of glucose and proteins in different animal groups. The plasma [K⁺] and [Na⁺], and ALP activity were significantly (P < < 0.05) elevated in F-treated animals, as compared with others. Administration of PP and Mel in F-treated rats caused significant (P < 0.05) reduction of [Na⁺], [K⁺], and ALP levels. Interestingly, PP and Mel administrations resulted in noticeable (P < 0.05) increases in the plasma glucose level in F-intoxicated animals, as compared to other groups. These findings convincingly indicate that PP and Mel exert ameliorative effects on fluoride-induced adverse changes in certain biochemical parameters in rats.